1204 Occupational exposure assessment to bioaerosols in poultry farming activities. (24th April 2018) - Matuka, DO; Singh, TS; Ratshikhopha, E; Dayal, P; Baatjies, R; Ngajilo, D; Jeebhay, MF
Abstract : Introduction: Poultry farm workers are exposed to various hazardous biological agents in organic dust. Particulate dust, endotoxins and (1–3) β-d-glucans) in poultry dust have been implicated in adverse respiratory effects including work-related asthma. Method: The study was conducted at various sites of a South African poultry farm consisting of broilers, rearing, laying, hatchery and catching processes. Personal inhalable samples were collected from 298 workers using filtration technique at a flow rate of 2 l/min for the entire work shift. Filter extracts were analysed for (1–3) β-d-glucan and endotoxin using the endpoint Glucatell and Limulus amebocyte lysate test (LAL) assays, respectively. Total inhalable dust concentration was also determined. Data were analysed using STATA 12. Results: Dust particulate levels had an overall geometric mean (GM) of 11.04 mg/m 3 and differed by farm process The mean dust particulate concentration was highest in the rearing department (GM=54.04 mg/m 3, GSD=3.74) followed by hatchery (GM=36.25 mg/m 3, GSD=3.46). The automated egg laying farms recorded elevated concentrations of dust particulate (GM=35.23 mg/m 3 ), endotoxin (GM=880 EU/m 3 ) and (1–3) β-d-glucan (GM=136 ng/m 3 ) levels compared to the manual laying system (GM=3.95 mg/m 3 ; GM=680 EU/m 3 ; GM=97 ng/m 3 ). Large broilers had relatively higher total dust particulate and endotoxin concentrations while small broilers had higher (1–3) β-d-glucan levels. The catching crew were found to have the highest concentrations of (1–3) β-d-glucan (GM=644 ng/m 3, GSD=1.89) and endotoxin levels (GM=23902 EU/m 3, GSD=9.64). Discussion: This exposure characterisation study revealed that total inhalable dust, endotoxin and (1–3) β-d-glucans were very high and significantly variable between the five main poultry farming processes. Workers in all processes were exposed to endotoxin levels above the recommended OEL of 90 EU/m 3 . Inhalable dust particulate was also above the 10 mg/m 3 OEL for total inhalable dust in the hatchery, rearing and automated laying farms. Poultry catchers appear to be at greatest risk of developing adverse respiratory health effects due to endotoxins and (1–3) β-d-glucans.